Translocação de chumbo em feijão comum (Phaseolus vulgaris L.) cultivados em adubos orgânicos produzidos com Salvinia auriculata Aubl. (Salviniaceae) e Cabomba caroliniana A. Gray (Cabombaceae) dos Marimbus-Andaraí-Chapada Diamantina-Ba-Brasil - Lima, Adriano Cosme Pereira (2017)
Over the past few years, lentic environments have been suffering from the degradation of the quality and quantity of their waters, due to intense anthropogenic activity. However, studies from the analyses of heavy metals in water, sediments and aquatic macrophytes constitute one of the fundamental steps for lentic environment management and monitoring, since they represent major natural resources for various activities in the economy, health, landscaping, and even in the cycling of nutrients. As a part of this ecosystem, the aquatic macrophytes can, due to their great production of biomass, be reused in agriculture as organic fertilizers by means of composting. Organic fertilizers exert great physical, chemical, and biological benefits to the soil and vegetation. However, the heavy metals that come from fertilized chemicals, when used indiscriminately, can accumulate in excess in the tissue of aquatic macrophytes. This can make their use as organic fertilizers inviable, because they can be translocated to the edible parts of the vegetation, such as the bean grains, causing serious health risks to humans and animals. In this sense, this work had as an aim: quantify the level of heavy metals in the compartments (water, sediments, Salvinia auriculata, and Cabomba caroliniana) from the Marimbus wetlands; characterize the organic fertilizers stemming from aquatic macophytes and determine the presence of the heavy metals Pb and Cd in the bean grains according to the relevant legislation for each material. Samples were collected from water, sediments, S. auriculata and C. caroliniana. The process of aerobic composting with macrophytes was done in which the levels of pH, temperature, nutrients and humidity were analyzed. The planting of the common bean (Phaseolus vulgaris L.) was effectively implemented with organic fertilizers coming from the macrophytes. Subsequently, in each step, heavy metals were analyzed in samples of water, sediments, Salvinia auriculata, Cabomba caroliniana, organic fertilizers and bean grains through the air-acetylene flame atomic absorption spectrophotometry method. In relation to water and sediments, the results obtained showed that the levels of heavy metals are within the limits established by the current legislation. The raw materials used as substrates in the composting showed satisfactory physical and chemical parameters as organic components to be applied in agricultural activities. As to the presence of heavy metals in bean grains, a Ph was detected with inadequate levels for human consumption. Thus, it was concluded that the macrophytes are of vital importance to guarantee the various uses of water in the hydric sources as well as viable for the production of organic fertilizers, but they should be used in agriculture with restrictions.